Perjumpaan Ekumenis dalam Komunitas Doa dengan Nyanyian Taizé (DNTZ) UKDW - Andreas Agung Yubile; Ferdy Rudy Bahari Nadeak; Krisnandi Candra Wijaya (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2025)
Nowadays, the awareness and call to build unity, especially within the Church, is becoming increasingly stronger. The efforts to realize this unity are not only present among theologians or Church leaders but are also lived out by the congregation in even the simplest forms. This article discusses the importance of Christian unity in the ecumenical movement through the Taizé Prayer and Song Community (DNTZ) at Duta Wacana Christian University (UKDW). Based on Jesus’ prayer in John 17:21, this ecumenical movement aims to restore the unity of divided churches through prayer and cross-denominational collaboration. The research method used is descriptive qualitative, employing a literature study approach and complemented by interviews with DNTZ UKDW community activists. The article is enriched with analyses based on Yves Congar’s thoughts on ecumenism and Habermas’ thoughts on the public sphere. This article delves deeper into the ecumenical practices embodied in the DNTZ UKDW community, which serves as a new public space where people from various denominations can pray together and encounter one another. The research findings show that through Taizé songs, this community has successfully created an inclusive, meditative, and spiritual encounter space that transcends denominational and theological boundaries. This unity in prayer demonstrates significant potential in fostering cross-church dialogue and cooperation including social movements, making DNTZ a living and real ecumenical model.AbstrakDewasa ini, kesadaran dan panggilan untuk membangun kesatuan terutama dalam lingkup Gereja semakin kuat. Usaha perwujudan tersebut tidak hanya ada dalam kalangan para teolog atau petinggi Gereja tetapi juga dihidupi oleh umat dalam bentuk sederhana sekalipun. Artikel ini membahas pentingnya kesatuan umat Kristen dalam gerakan ekumenis melalui komunitas Doa dengan Nyanyian Taizé (DNTZ) di Universitas Kristen Duta Wacana (UKDW). Berlandaskan pada doa Yesus dalam Yohanes 17:21, gerakan ekumenis ini bertujuan memulihkan kesatuan gereja-gereja yang terpecah melalui doa dan kolaborasi lintas denominasi. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan pendekatan studi kepustakaan serta dilengkapi dengan wawancara dari pegiat komunitas DNTZ UKDW. Artikel ini turut diperkaya dengan analisis berdasarkan pemikiran Yves Congar mengenai ekumenisme dan Habermas mengenai ruang publik. Kajian ini hendak menggali lebih dalam tentang praktik ekumenis yang diwujudkan dalam komunitas DNTZ UKDW, yang berfungsi sebagai ruang publik baru di mana umat dari berbagai denominasi dapat berdoa bersama dan saling berjumpa. Hasil penelitian menunjukkan bahwa melalui nyanyian Taizé, komunitas ini berhasil menciptakan ruang perjumpaan yang inklusif, meditatif, dan spiritual, yang melampaui batasan denominasi dan teologi. Kesatuan dalam doa ini menunjukkan potensi besar dalam membangun dialog dan kerja sama lintas-gereja termasuk gerakan sosial, menjadikan DNTZ sebagai model ekumenis yang hidup dan nyata.